A note on the insecticide susceptibility status of secondary malaria vector An. annularis in Jharkhand state of India - M K Das; Manju Rahi; Gaurav Kumar; K Raghavendra (Journal of Vector Borne Diseases, 2022)
Background & objectives: An. annularis van der Wulp (1884) is the secondary malaria vector of importance in India. In Jharkhand state it is present in almost all the districts abundantly and transmits malaria. The development of resistance to Dichlorodipheny ltrichloroethane (DDT) in An. annularis was reported from various parts of India. The main objective of this study was to generate information on insecticide susceptibility status of An. annularis to DDT, malathion, deltamethrin and permethrin in different districts of Jharkhand state. Methods; Adult An. annularis female mosquitoes were collected form villages of six tribal districts Simdega (Kurdeg and Simdega CHC), Khunti (Murhu and Khunti CHCs), Gumla (Bharno and Gumla CHCs), West Singhbhum (Chaibasa and Bada Jamda CHCs), Godda (Poraiyahat and Sunderpahari (CHCs) and Sahibganj (Borio and Rajmahal CHCs). Insecticide susceptibility status was determined by using WHO tube test method against prescribed discriminatory dosages of insecticides, DDT - 4.0%, malathion - 5.0%, deltamethrin - 0.05% and permethrin - 0.75%. Results: An. annularis was reported resistant to DDT in six districts, possible resistant to malathion in districts Gumla, Khuntiand Sahibganj and susceptible to deltamehrin (98% to100% mortality) and permethrin (100% mortality). Interpretation & conclusion: An. annularis, the secondary vector species is associated with the transmission of malaria reported resistant to DDT and susceptible to pyrerthroids deltamethrin and permethrin. In view of large-scale distribution of long-lasting insecticidal nets (LLINs) in all the districts, the response to synthetic pyrethroid needs to be periodically monitored to assess the effectiveness.